Awareness about cigarettes and other tobacco products act and impact of health warnings on smokers in a North Indian city - Gupta, Riya; Majeed, Mudasir; Langer, Bhavna; Kumari, Rashmi; Gupta, Rajiv Kumar; Mir, Mehak Taban (International Journal of Research in Medical Sciences, 2019)
Background: Tobacco use is a major preventable cause of morbidity as well as mortality worldwide. To combat the increasing trend of this problem, Government of India formulated the COTPA (Cigarettes and Other Tobacco Products Act) in 2003. The study aimed to assess the awareness about COTPA and impact of pictorial warnings among smokers attending outpatient services in a tertiary care hospital in Jammu. Method: The present study was conducted among 320 patients attending the outpatient department of Internal Medicine, Government Medical College, Jammu who happened to be cigarette smokers. The questionnaire was developed by authors with the help of literature review and pilot tested before its final use. Information was elicited about demographic details, awareness about COTPA and impact of pictorial warnings on quitting of smoking. Results: More than half of the respondents were in 30-50-year age group and were urban residents. Awareness about COTPA was good on some parameters but was relatively low on other parameters. Despite all, the respondents noticing pictorial warnings on tobacco packages, only 69.37% of them were contemplating to quit. About half of them were of the view that warning statements preferably be written in local languages. Conclusion: Health and pictorial warnings on tobacco packages remain an important pillar in filling the gap of knowledge and communicating the health risks of tobacco use to the consumers. Only 69.3% of the respondents were planning to quit and awareness levels about COTPA were mixed.